Father Collins with students at St. Joseph's School - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of Father Collins with students at St. Joseph's School. The pronounced speckling and streaking located on the far left side of the image is due to the degradation of the original nitrate film.